2011
DOI: 10.1093/neuonc/nor038
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance spectroscopic detection of lactate is predictive of a poor prognosis in patients with diffuse intrinsic pontine glioma

Abstract: Diffuse brainstem glioma has a poor prognosis, and there are few long-term survivors. We looked for clinical, conventional magnetic resonance (MR), and MR spectroscopic (MRS) findings predictive of the prognosis of patients with brainstem glioma. Our institutional review board approved this retrospective study of 23 patients with diffuse intrinsic pontine or diffuse medullary brainstem glioma treated during the period 2000-2009. To evaluate prognostic values, we performed a Kaplan-Meier survival analysis (log-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 53 publications
(34 reference statements)
7
58
0
1
Order By: Relevance
“…Assessment of this spectral region has also been helpful for distinguishing cancerous from non-malignant pathology from the brain [5,[7][8][9], and from other organs, such as the ovary [52] and the breast [53,54]. However, in vivo proton MRS studies [24,52] indicate that much uncertainty arises in attempts to assess this chemical shift region. We have seen from the Padé-reconstructed "ersatz" component spectra that in addition to the Lac doublet, a number of other resonances are closely overlapping even at a long TE of 272 ms, when the broad lipid resonances have already decayed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessment of this spectral region has also been helpful for distinguishing cancerous from non-malignant pathology from the brain [5,[7][8][9], and from other organs, such as the ovary [52] and the breast [53,54]. However, in vivo proton MRS studies [24,52] indicate that much uncertainty arises in attempts to assess this chemical shift region. We have seen from the Padé-reconstructed "ersatz" component spectra that in addition to the Lac doublet, a number of other resonances are closely overlapping even at a long TE of 272 ms, when the broad lipid resonances have already decayed.…”
Section: Discussionmentioning
confidence: 99%
“…At short echo times, Lac and Lip overlap since they both resonate in the chemical shift region of ∼1.3 ppm. Difficulties in identifying these two diagnostically important resonances are frequently encountered at short TEs [23,24]. The accurate assessment of Lac and Lip is recognized to be tenuous, due to the overlap of these resonances.…”
Section: Ensuing Diagnostic Dilemmasmentioning
confidence: 99%
See 1 more Smart Citation
“…An MRS study in humans has suggested that the levels of several metabolites, such as lactic acid and choline, are elevated in malignant gliomas (12). Another MRS study demonstrated no difference in glycine levels between glioblastoma and meningioma patients, although these levels were altered according to the grade of the glioma (22).…”
Section: Discussionmentioning
confidence: 99%
“…Various metabolites, such as amino acids and choline, have been analyzed in human glioma patients by means of proton magnetic resonance spectroscopy (MRS) or from tissue specimens obtained during surgery or autopsy (12,13). However, there have been few reports on PFAA analysis in intracranial disorders (14).…”
Section: Introductionmentioning
confidence: 99%